(untitled) (Journal of Oriental Studies, 2022)
Language is the main means of intercultural communication. In the era of globalization, the interweaving of different civilizations takes place through language. In this regard, the concepts of world language and international language also appeared. China, like Western countries among the developed countries, is actively spreading its national language around the world in order to turn it into a world language. The main purpose of this article is to determine the implementation of the Chinese language dissemination policy in the Middle Kingdom, the ways of spreading the language and the result. Methods of differentiation, classification and systematization of sources in Chinese and materials in Kazakh and English were used as research methods. The results of the research show that the language dissemination policy is an integral part of the foreign language policy. It can be carried out secretly and openly. The main way to spread the language is through the educational sphere, that is, through educational organizations and institutions. The successful implementation of the language dissemination policy directly depends on the financial fund allocated by the state. The country, with its growing economic potential, seeks to increase its influence on the world stage by spreading its national language around the world. After all, it becomes a part of foreign policy that not only establishes communication through language, but also forms its national image (image), leaving an imprint on its culture by assimilating it to others. Keywords: Chinese, language distribution, Confucius Institute, One Belt, One Road